2014
DOI: 10.3892/ol.2014.2355
|View full text |Cite
|
Sign up to set email alerts
|

Staging laparotomy for endometrial cancer in a patient with situs inversus totalis: A case report

Abstract: Situs inversus is a rare congenital anomaly in which the organs are transposed from their normal site to the opposite side of the body. To the best of our knowledge, this is the first study of staging laparotomy performed in a patient with endometrial carcinoma and situs inversus totalis (SIT). This study presents a patient with early endometrial carcinoma with SIT who underwent staging laparotomy. Total abdominal hysterectomy with bilateral salphingoophorectomy, omentectomy and pelvic para-aortic lymph node d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Notably, preoperative information on blood vessels can be obtained radiographically, and pelvic lymphadenectomy is preferred. In this study, preoperative evaluation using 3D-CT images showed promising results in the treatment of SIT patients [15].…”
Section: Discussionmentioning
confidence: 67%
“…Notably, preoperative information on blood vessels can be obtained radiographically, and pelvic lymphadenectomy is preferred. In this study, preoperative evaluation using 3D-CT images showed promising results in the treatment of SIT patients [15].…”
Section: Discussionmentioning
confidence: 67%